Conference Report:International Conference on Forced Migration and Refugee Studies: issues and shifting paradigms, 5-7 December, 2017 (Tuesday-Thursday) 17-19 Rabi al-Awwal 1439 - Hossain, Ishtiaq (IIUM Press, International Islamic University Malaysia, 2017)
The world is currently facing its biggest refugee crisis since the end of Wold War II. According to the UN refugee agency a record 65.6 million people are either refugees, asylum seekers or Internally Displaced Persons (IDPs). The world witnessed an unending stream of refugees fl eeing the violence in Syria, Iraq, and Afghanistan to Europe. In the meantime, thousands of illegal migrants, mostly from the West African region, continue to try to reach the shores of Europe. Many of these migrants, while trying to reach Europe, have drowned in the Mediterranean. Recently videos have appeared in the international media showing auction of human beings as slaves.